Acusana DeLong (Hemiptera: Cicadellidae: Gyponini), a genus not previously recorded in Brazil: description of four new species for the Brazilian fauna - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2019)
The genus Acusana is recorded from the Brazilian fauna for the first time, with the description of four new species: Acusana adunca sp. nov. and Acusana spina sp. nov. from Mato Grosso, Central-Western Brazil and Acusana dilatata sp. nov. and Acusana longa sp. nov. from Maranhão, Northeast Brazil. Detailed description and illustrations of male and female are provided, as well a revised diagnosis for the genus. The female genitalia of Acusana species is described and illustrated by the first time. A new record of Acusana paga DeLong & Freytag, 1966 is added from Costa Rica.